Sexual Assault Response Team (SART) Implementation and Collaborative Process: What Works Best for the Criminal Justice System? 2010-2013 (UNITED STATES) - Campbell, Rebecca ([Verlag nicht ermittelbar], 2016)
Sexual Assault Response Teams (SARTs) are interventions that were created to coordinate efforts of the legal, medical, mental health systems, and rape crisis centers, in order to improve victims' help seeking experiences and legal outcomes. This study examined the relationship between SART structure and effectiveness by conducting a national scale study of SARTs and a smaller detailed network analysis of four SARTs.